Polyphasic Characterization of Bipolaris maydis: Insights into Pathogen Identity and Variability through Morpho-cultural and Molecular Traits - Monisha, M.; Pankaja, N. S.; Sunitha, Mummineni; Mahadeva, J.; Kumar, Umashankar; Supriya, S. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the March–June, 2022 at College of Agriculture, V. C. Farm, Mandya, Karnataka, India to study Polyphasic characterisation of Maydis leaf blight (Bipolaris maydis) which accounts for 30–40% of yield loss. Isolates were collected in October 2021 during survey within four districts of Karnataka. Morphological studies revealed that mycelia and conidia of all the twenty isolates were brown in colour and septate. Conidial size among the isolates varied from 57.44–80.05×11.34–15.77 µm being either curved or fusiod. Variation in colony colour was observed viz., grey to blackish grey. Two isolates BmCKD, BmMNG produced light grey, six isolates BmRDK, BmGLG, BmRCH, BmNYP, BmBDH, BmDHM produced grey, four isolates BmHSK, BmHNG, BmMDH, BmDHM produced dark grey and eight isolates BmZARS, BmMNY, BmHKP, BmADH, BmSVN, BmSNG, BmTNP, BmNVL produced greyish black color colony on PDA. Among nine different solid media used, maximum mycelial growth of 71.06 mm was observed in maize leaf decoction with PDA medium and minimum mycelial growth of 37.33 mm in Richard’s Agar. Further, sporulation of conidia was earliest (48–84 hrs.) in maize leaf decoction with PDA and delayed (120–168 hrs.) in V8 Juice Agar media. Sequence analysis with ITS1 and ITS4 primers revealed that of all the isolates showed similarity with B. maydis and showed relatively low E-value of zero depicting the highest confidence level. Maximum of 100% similarity was observed in BmHKP, BmRDK, BmSNG, BmTNP, BmBDH and BmUPH isolates.